Influence of Classroom Environment on the Academic Performance of Students in English Language - Benjamin F.C. Nwokedi (MultiTech Publisher, 2023)
The classroom environment plays a pivotal role in the academic performance and engagement of students, particularly in the realm of English language learning. This study explored the perceived influence of various classroom environmental factors on the academic performance of students in English language. Factors such as the physical environment, teacher-student interactions, peer interactions, teaching strategies, and assessment techniques were examined. A mixed-method approach, encompassing surveys and focus group discussions, were employed to gather perceptions from both students and teachers in a diverse urban secondary school. The findings suggest that a conducive physical environment, positive interpersonal relations, innovative teaching strategies, and fair assessment practices significantly impact students’ motivation and performance in English language. Recommendations for improving the classroom environment to foster better language acquisition and academic performance were made. This study contributes to the broader understanding of how the classroom environment shapes the learning experiences and academic outcomes of students in the context of English language education.